Evaluating bioclimatic aspects over the Vidarbha region - SARKAR, JAYANTA; GADGIL, A. S. (MAUSAM, 2004)
Some of the important bioclimatic aspects, outgoing water budget from the human body in terms of respiratory and non-respiratory evaporative losses, human discomfort and wind chill have been studied in this paper. Outgoing water budget has been computed using monthly normals of the maximum temperature and vapour pressure for a number of fairly well distributed stations in the Vidarbha region. Discomfort has been quantified using Thom’s (1959) Temperature-Humidity Index (THI) or Discomfort Index and wind chill aspects have been studied using the ‘wind chill index (WCI)’ of Siple and Passel (1945). The study reveals that total water loss from the human body, sum of respiratory and non-respiratory losses, is maximum (384 g. day-1) in summer and minimum (116 g. day-1) in monsoon. However, highest respiratory loss of 213 g.day-1 is observed in winter and that of lowest (66 g. day-1) in monsoon. Sensible sweating is very much felt in summer. However, it is not at all felt in winter and post monsoon. Though mornings are comfortable in March, yet the entire region starts experiencing discomfort in the evening hours. As expected, in April and May maximum discomfort prevails. Buldhana district, in the western part of the study region, remains comfortable both during winter and summer in the morning hours. Average cooling power over Vidarbha in winter is observed to be 342 W/m2. At Nagpur, maximum cooling power (389 W/m2) has been noticed in this season. Isopleth analysis of monthly mean hourly wind chill reveals that in peak winter (December and January) only during 1300-1700 hours Nagpur climate is ‘pleasant’ and rest of the day is ‘cool’ to ‘very cool’. However, in peak summer (May) only during 0400-0600 hours climate is ‘pleasant’ and remaining part of the day is ‘warm’ to ‘hot’. Even in April, despite its being a prominent summer month, climate remains ‘cool’ from 0300 to 0700 hours.